CONTRIBUTION OF THE SCIENTIFIC AND TEACHING ELITE OF THE UKRAINIAN DIASPORA OF THE WESTERN UKRAINIAN LANDS TO THE PRESERVATION AND ENRICHMENT OF THE CULTURAL HERITAGE OF UKRAINE DURING THE INTERWAR PERIOD - Сабардак, Ярослав (SWorldJournal, 2024)
The work examines and emphasizes the significance of the contribution of historians and the scientific and teaching elite of Western Ukrainian lands in the context of preserving the cultural heritage of Ukraine. The period of study consists of the years b